Isolation, Molecular Identification, and Antibiogram of Gut Bacteria of Paradise Threadfin from the Tetulia River, Bangladesh (Bangladesh Journal of Microbiology, 2025)
The paradise threadfin, Polynemus paradiseus, is an anadromous fish in Bangladesh that enters the freshwater river system from saline water (the Bay of Bengal) to spawn. The gut bacteria of paradise threadfin were characterized both physiologically and molecularly, and their antibiogram profile was formulated after collection from the Tetulia River, Bhola, Bangladesh. A total of 24 isolates were identified under the genera Bacillus, Salmonella, Brucella, Enterobacter, Citrobacter, Pseudomonas, and Kluyvera. Pseudomonas was one of the most dominant genera based on bacterial abundance in the gut of P. paradiseus. The majority of bacterial isolates showed maximum growth between 30 and 40 °C and at pH 8.5. All of the strains were multidrug resistant and showed up to 100% resistance to cefixime, penicillin, ampicillin, and neomycin. Strains of Enterobacter, Citrobacter, Kluyvera, and Pseudomonas showed 100% resistance to seven antibiotics.Bangla. J. Microbiol. 2025, Vol. 41, P: 1-6